PENGEMBANGAN UMKM KERIPIK TIKE MELALUI MANAJEMEN USAHA DI DESA DOMAS SERANG BANTEN - Remvilina Sari; Siti Nurjanah; Ahmad Ramdani; Ende Ende (Gapenas Publisher, 2021)
The Student Work Lecture Program is one of Bina Bangsa university programs as one of Tri Dharma Higher Education implementations, namely student service to the community to help and guide the community in utilizing resources that are expected to help develop the potential of the community. This program aligns research and community service activities from lecturers and students across science and brings togetherness values. This implementation is an effort to develop Micro, Small, and Medium Enterprises tike chip products to increase competitiveness as a typical regional food product that consumers demand through improvements in business management. By the problems these partners face, the efforts that can be made are improvements in business management through marketing, production, and financial aspects. The specific target of this activity is 1) improvement of business management through improvement of marketing strategies; 2) improvement of the production process; 3) The neatness of financial records. The methods used in this activity are socialization, training, and mentoring. The solution provided to the problem of marketing aspects is the expansion of offline market reach in stores and minimarkets around and the use of online marketing information technology through e-marketplaces and social media applications. In addition, the use of brands in the form of stickers/labels also helps expand market share. Problem-solving in the production aspect is done by creating product innovation through flavour and packaging variations in the manufacture of tike chip products supported by more attractive and competitive packaging that can help solve problems in the production aspect. Financial aspects, problem-solving is done through socialization, training, and mentoring in recording financial transactions, both income, and expenditure, to produce simple financial bookkeeping, to know business income in a measurable per certain period.